La petite histoire du travail invisible - L'R des centres de femmes du Québec (2019)
La petite histoire du travail invisible Voici notre vidéo sur les luttes féministes pour la reconnaissance du travail invisible! Elle est inaugurée en cette Journée nationale des centres de femmes du Québec #JNCF2019. Allez dans un centre près de vous pour continuer la lutte avec nous!Avec la participation L'R des centres de femmes du
Keywords: 1900-1999; 1960-1969; 2000 à aujourd'hui; 2010-2019; approches et analyses; discipline; foyer; groupes de femmes; histoire et politique; inégalités; justice sociale; militance; périodes historiques; ressource en ligne; sciences humaines; stage; systèmes d'oppressions; thématiques; travail; travail social

In the name of women's rights: the rise of femonationalism - Farris, Sara R. (Duke University Press, 2017)
Sara R. Farris examines the demands for women's rights from an unlikely collection of right-wing nationalist political parties, neoliberals, and some feminist theorists and policy makers. Focusing on contemporary France, Italy, and the Netherlands, Farris labels this exploitation and co-optation of feminist themes by anti-Islam and xenophobic campaigns as “femonationalism.” She shows that by characterizing Muslim males as dangerous to western societies and as oppressors of women, and by emphasizing the need to rescue Muslim and migrant women, these groups use gender equality to justify their racist rhetoric and policies. This practice also serves an economic function. Farris analyzes how neoliberal civic integration policies and feminist groups funnel Muslim and non-western migrant women into the segregating domestic and caregiving industries, all the while claiming to promote their emancipation. In the Name of Women's Rights documents the links between racism, feminism, and the ways in which non-western women are instrumentalized for a variety of political and economic purposes.
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; approches et analyses; cours; discipline; europe; france; féminisme islamique; fémonationalisme; histoire et politique; intersectionnalité; italie; justice sociale; pays-bas; pol4212; premier cycle; périodes historiques; racisme; régions géographiques; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques